‘We’re all in this together’: the protective role of belongingness in the contribution of moral injury to mental health among participants in Israel’s civil protest movement - Yossi Levi-Belz; Yoav Groweiss; Iris Shachar Lavie; Yael Shoval Zuckerman; Carmel Blank (European Journal of Psychotraumatology)
Background: Participating in long-term protests against government actions can affect protesters’ mental health and expose protesters to potentially morally injurious events (PMIEs), such as the betrayal by leaders they once trusted. This study aimed to shed light on the potential psychological buffers against the deleterious effects of exposure to PMIEs of betrayal among protesters and to examine the moderating role of belongingness in the relationships between protesters’ exposure to PMIEs and stress, PTSD and depression levels.Method: The study sample comprised 4036 Israeli protesters (Mage = 54.27, SD = 12.45; 75.6% females) who took part in the unfolding civil protest movement against the government-led judicial and constitutional overhaul between January 2023 and August 2023. Protesters completed validated self-report questionnaires that included measures of PMIEs, stress, depressive and PTSD symptoms (PTSS).Results: Beyond demographic and protest-related characteristics, exposure to PMIEs of betrayal was found to contribute to both PTSD and depression levels. The indirect effects of PMIE-betrayal on PTSS/depressive symptoms through stress levels were significant, particularly when belongingness levels were low. Thus, a greater sense of PMIE-betrayal contributes to stress symptoms, which, in turn, is linked to higher levels of PTSS and depressive symptoms for protesters having low levels of belongingness.Conclusions: The study’s findings highlight the critical contribution of PMIE-betrayal to both PTSS and depression levels, which were mediated by levels of stress. Moreover, experiencing belongingness moderated these relationships. Clinicians treating protesters coping with PTSS and depressive symptoms should also adopt therapeutic aims of establishing belongingness and social support among the protesters.